Friends of libraries sourcebook - Dolnick, Sandy (American Library Association, 1996)
Greatly expanded, this third edition is your one-stop resource for organizing and managing your library's valuable Friends group. Editor Sandy Dolnick, the leading Friends authority, supplies vital tools and tips to coordinate your library's Friends and explains the intricacies of the Section 501 (c)(3) tax exempt status for cost-effective fundraising. Packed with real-life examples of how Friends from around the country support their library, this handy guide also includes appended information on gift shops, sample constitutions, and Friends of Libraries U.S.A. Fact Sheets.